Singenetic Avalanche In The Ukrainian Carpathians - Тиханович, Є. Є.; Біланюк, В. І.; Фігурний, Д. В. (Man and Environment. Issues of Neoecology, 1970)
Purpose. Study of natural conditions of formation and passage of avalanche situation until the avalanche’s going within the North-Eastern macro-slope of Chorohora and Borzhava landscapes. Methods: fieldwork, GIS modeling, cartographic and statistical methods. Results. Describe main genetic types of avalanche on the Ukrainian Carpathians limit and their affect characteristic on formation of avalanche situation. Investigate some snowfall and blizzard affect conditions on the snow cover stability. The special feature of syngenetic avalanche slide in mountain range Chornogora and Borgava is analyzing. The place of this territory in the physico-geographic regionalization is constituted. Research the snow types and stratigraphy structure which are forming within limits of Chornogora and Borgava nature regions. Particularity of meteorological characteristics and phenomena by avalanche situation development is study. Investigate influence of ground surface on avalanche slide. Determine numerical importance by temperature, wind and other characteristics under the terms are fix avalanche. Describe snowfall intensity during avalanche period. Analyzing special feature of snow cover stratigraphy structure, that are typical for syngenetic avalanche and number of snow layer before slide. Determine avalanche regime in Ukrainian Carpathians. Conclusions. Syngenetic avalanche in the Ukrainian Carpathians provoked snowfall confined to the slopes of different exposures. Meteorological conditions of avalanche situations vary depending on the avalanche mode.